2021
DOI: 10.1177/15910199211014701
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of carotid cavernous sinus fistulas with flow diverters. A case report and systematic review

Abstract: Introduction Carotid cavernous fistulas (CCFs) are rare, usually follow head trauma or aneurysmal rupture. Recent treatment options include endovascular techniques such as flow diversion devices (FDDs). Objective To present our case treated with FDD application with transarterial cavernous-sinus coiling and present a systematic review on the use and effectiveness of FDDs in CCF treatment. Materials and methods We present our case of CCF treatment with FDD. A search was also conducted in PubMed, EMBASE and Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…[18] In fact, flow diverters are designed with specific properties and their composition enables to preserve side arterial branches from occlusion. [18] e time required for achieving a fistula occlusion represents a disadvantage in preventing a rapid symptoms improvement after treatment. As regards to indirect fistulas, Castaño et al reported two cases of Barrow B-type of CCFs successfully treated with flow diverter stent in the left ICA in both cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] In fact, flow diverters are designed with specific properties and their composition enables to preserve side arterial branches from occlusion. [18] e time required for achieving a fistula occlusion represents a disadvantage in preventing a rapid symptoms improvement after treatment. As regards to indirect fistulas, Castaño et al reported two cases of Barrow B-type of CCFs successfully treated with flow diverter stent in the left ICA in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the treatment should be the occlusion of the fistula site or at least the reduction to minimum of the residual arterial blood flow into the venous system while preserving the patency of ICA and its arterial branches. [ 18 , 19 ] Therapeutic approaches for CCFs followed the same transition through technological development. Historically, traditional maneuvers included manual compression of the CCA and jugular vein, and external ocular compression of the angular vein with or without carotid compression, with a rate of complete occlusion around 30%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FDDs are becoming more important in aneurysmal treatment due to the significant intraoperative complications associated with open surgical approaches, the shallow nature, the shape of the aneurysms, and the natural tortuosity in some vessels such as the ICA, which renders stent-assisted coiling ineffective. [1,17] FDDs are new-generation stents used primarily in large and giant aneurysms, wide-necked, and recurrent aneurysms. [14] ey are used for saccular, fusiform, and blister-type ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…FDDs are becoming more important in aneurysmal treatment due to the significant intraoperative complications associated with open surgical approaches, the shallow nature, the shape of the aneurysms, and the natural tortuosity in some vessels such as the ICA, which renders stent-assisted coiling ineffective. [ 1 , 17 ]…”
Section: Discussionmentioning
confidence: 99%